2009
DOI: 10.1177/0959683609345085
|View full text |Cite
|
Sign up to set email alerts
|

Holocene benthic foraminifera from Bahía Blanca estuary: a review and update of systematic and palaeoenvironmental aspects

Abstract: Assemblages of benthic foraminifera in a Holocene core from the outer area of Bahía Blanca estuary in Argentina were studied. The systematic of the group was updated, and provided 28 genera distributed among 59 species, six species with nomenclature aperta. The main species recorded were Buccella peruviana f. campsi (Boltovskoy), Ammonia beccarii (Linné), Elphidium gunteri Cole, Elphidium galvestonense Kornfeld, Elphidium articulatum d’Orbigny and Elphidium discoidale (d’Orbigny). These species allowed an estu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
15

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 28 publications
2
15
0
15
Order By: Relevance
“…They are most common at the bottom of clear lakes, usually forming extensive growths (Lee, 2008). Several studies applying these groups in paleoenvironmental reconstructions have been carried out on the Pampa coastal plain (Bertels & Martínez, 1990, 1997Laprida & Bertels-Psotka, 2003;Fontana, 2004;Gómez et al, 2005Gómez et al, , 2006Laprida et al, 2007;Cusminsky et al, 2009;Ferrero, 2006Ferrero, , 2009Marquez & Ferrero, 2011;Calvo-Marcilese et al, 2011.…”
Section: Introductionmentioning
confidence: 99%
“…They are most common at the bottom of clear lakes, usually forming extensive growths (Lee, 2008). Several studies applying these groups in paleoenvironmental reconstructions have been carried out on the Pampa coastal plain (Bertels & Martínez, 1990, 1997Laprida & Bertels-Psotka, 2003;Fontana, 2004;Gómez et al, 2005Gómez et al, , 2006Laprida et al, 2007;Cusminsky et al, 2009;Ferrero, 2006Ferrero, , 2009Marquez & Ferrero, 2011;Calvo-Marcilese et al, 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Examination of subsurface sediment and core data clearly indicate, however, that the species was absent from the estuary for at least the last 8,200 years BP (Calvo-Marcilese unpublished data; Cusminsky et al 2009). In addition, large-scale comprehensive surveys of recent benthic foraminifera showed that H. germanica has never been reported in modern environments along the southwestern Atlantic coast of Argentina and Brazil (summarized in Boltovskoy et al 1980).…”
Section: Discussionmentioning
confidence: 96%
“…Oscilaciones entre los cal. 2.700-2.330 años AP y entre los cal 4100-3750 años AP aproximadamente, fueron reconocidas en Brasil (Martin et al, 2003; entre otros), mientras que en el área de Bahía Blanca, Argentina, Gómez et al (2005bGómez et al ( , 2006 y Cusminsky et al (2009) reconocen oscilaciones del NMM por debajo del actual para los cal. 7.300-6.600 años AP (A) y los cal.…”
Section: Cambios Del Nivel Medio Del Mar Durante El Holoceno En El Esunclassified